Survey On The Implementation Of Physical Education Health And Recreation Learning After The Covid 19 Pandemic At Smp Negeri 4 Pelalawan - Anggi Pratama; Oki Candra; Toktong Parulian (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Objective Research conducted is for know Implementation learning corner After the Covid-19 Pandemic in SMP Negeri 4 Pelalawan. Type study This is descriptive purposive qualitative give description systematic about moderate condition taking place on object study after the Covid-19 pandemic at SMP Negeri 4 Pelalawan. Population on study This is student senior high school country 4, numbering 40 people. Determination sample in study This done with total sampling that is technique taking  sample where all over its population made sample all . Difficult instrument respondents as many as 40 questions. After the questionnaire created, questionnaire moreover formerly validated by 3 validators, namely language validator, psychology validator, and educational validator physical. After validation by 3 validators, carried out test Try the instrument at a school that has it the same characteristics with sample study namely SMP Negeri 4 Pelalawan . Based on results study so obtained conclusion that is Survey Implementation Learning Corner After the Covid-19 Pandemic in SMA Negeri 4 Pelalawan classified  tall with an average of 73.97% located on range percentage between 61-80% which means in a way whole in  implementation learning corner after covid-19 pandemic in SMP Negeri 4 Pelalawan Already own good interest.